Health Inequality and Health Insurance Coverage: The United States and China Compared - Joan Costa-Font; Frank Cowell; Xuezhu Shi (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study inequality in the distribution of self-assessed health (SAH) in the United States and China, two large countries that have expanded their insurance provisions in recent decades, but that lack universal coverage and differ in other social determinants of health. Using comparable health survey data from China and the United States, we compare health inequality trends throughout the period covering the public health insurance coverage expansions in the two countries. We find that whether SAH inequality is greater in the US or in China depends on the concept of status and the inequality-sensitivity parameter used; however, the regional pattern of SAH inequality is clearly associated with health-insurance coverage expansions in the US but not significant in China.
Keywords: D63; I18; I30; 330; health inequality; self-assessed health; health insurance coverage; social determinants of health